2014
DOI: 10.1177/1934578x1400900905
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids from Fagonia mollis

Abstract: A new acyclic diterpenoid (1) and a new erythroxan diterpenoid (2), together with 4 erythroxan diterpenoids and 3 triterpenoids, have been isolated from the aerial parts of Fagonia mollis. Their structures were elucidated on the basis of 1D and 2D NMR data. The cytotoxic activity of the isolated compounds was investigated against HL-60 cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A total of forty-nine triterpenoid saponins (1-49) have been identified in the five investigated Fagonia species, F. arabica L. (Miyase et al, 1996a;Shoeb et al, 1994;Perrone et al, 2007), F. cretica L. (Abdel Khalik et al, 2000aBatterjee et al, 2002;Anjum et al, 2014;Saleem et al, 2014), F. glutinosa Delile (Melek et al, 2000), F. indica Burm.f. (Ansari et al, 1987(Ansari et al, , 1988Shaker et al, 1999Shaker et al, , 2000Shaker et al, , 2013Farheen et al, 2015), and F. mollis Delile (Sallam et al, 2014). Their structures are reported in Table 1 and Fig.…”
Section: Previous Workmentioning
confidence: 96%
See 2 more Smart Citations
“…A total of forty-nine triterpenoid saponins (1-49) have been identified in the five investigated Fagonia species, F. arabica L. (Miyase et al, 1996a;Shoeb et al, 1994;Perrone et al, 2007), F. cretica L. (Abdel Khalik et al, 2000aBatterjee et al, 2002;Anjum et al, 2014;Saleem et al, 2014), F. glutinosa Delile (Melek et al, 2000), F. indica Burm.f. (Ansari et al, 1987(Ansari et al, , 1988Shaker et al, 1999Shaker et al, , 2000Shaker et al, , 2013Farheen et al, 2015), and F. mollis Delile (Sallam et al, 2014). Their structures are reported in Table 1 and Fig.…”
Section: Previous Workmentioning
confidence: 96%
“…Previous phytochemical studies on Fagonia species demonstrated the presence of flavonoids (Saleh et al, 1990;Al-Wakeel 1992;El-Wakil and Eman, 2007), diterpenoids (Abdel-Kader et al, 1993;Perrone et al 2007;Sallam et al, 2014), sterols glycosides (Shoeb et al 1994), triterpenes (Anjum et al, 2007;Saleem et al, 2014;Farheen et al, 2015) and saponins (Ansari et al, 1988;Miyase et al, 1996a;Melek et al, 2000;Batterjee et al, 2002;Sallam et al, 2014).…”
Section: Previous Workmentioning
confidence: 98%
See 1 more Smart Citation
“…The diterpenes from Callicarpa longissima (Liu et al , ), Clerodendrum splendens (Faiella et al , ), Fagonia mollis (Sallam et al , ), Icacina trichantha (Zhao et al , ), Hedychium longipetalum (Zhao et al , ), Micromonospora sp. (Mullowney et al , ), Cespitularia taeniata (Wang et al , ), Caesalpinia spinosa (He et al , ), Nephthea columnaris (Hsiao et al , ), Bursera microphylla (Messina et al , ), Teucrium viscidum (Gao et al , ), Euphorbia ebracteolata (Yuan et al , ), Euphorbia aellenii (Yazdiniapour et al , ), Perenniporia subacida (Wen et al , ), Abies fargesii (Wu et al , ) and Premna tomentosa (Rekha et al , ) were also evident to exert cytotoxic effects on a number of human cancer cell lines.…”
Section: Diterpenic Anticancer Traitsmentioning
confidence: 99%
“…This genus is present in Algeria with 17 species [2]. Several phytochemical studies of this genus showed the presence of flavonoids [3], diterpenoids [4,5], and triterpenoid saponins [6]. Fagonia longispina Batt.…”
mentioning
confidence: 99%